EFFECT OF INVOCATION (DO’A) ON PAIN-COPING BEHAVIORS OF PRIMIPAROUS MUSLIM WOMEN DURING THE FIRST THREE HOURS OF THE ACTIVE PHASE OF LABOR - Desmawati Desmawati (Belitung Raya Foundation, Indonesia, 2016)
Background: Pain-coping behavior of primiparous women may have adverse effects on the mother and fetus. In Tangerang, the majority of pregnant women have negative experiences of pain and pain-coping behaviors during labor. Objective: The purpose of this study was to examine the effect of the invocation (do’a) on pain-coping behaviors of primiparous Muslim women during the first 3 hours of the active phase of labor. Methods: It was an experimental study with pre-posttest design. Ten primiparous women were randomly selected and assigned to the control and intervention group. Each group consisted of 5 participants. Pain-coping behavior was measured by the Pain Behavior Observation Scale (POBS). Results: Findings revealed that pain-coping behaviors were increased for those who received the invocation (do’a) with p-value < .05 than those who received the routine care. The effectiveness of do'a could be seen from the average difference of scores of pain-coping behaviors before and after intervention. The intervention group significantly had higher pain-coping behaviors than the control group during three hours of posttest, while controlling for the pretest measure, F (3.24) = 15.68, p< .001. Conclusions: The invocation (do’a) program for primiparous women during labor is feasible to be conducted, and effective to increase pain-coping behaviors. Therefore, it is suggested to provide this program for primiparous women during the first 3 hours of active phase of labor.